Nonsupersymmetric Dualities from Mirror Symmetry - Kachru, Shamit (2017)
We study supersymmetry breaking perturbations of the simplest dual pair of (2+1)-dimensional N=2 supersymmetric field theories - the free chiral multiplet and N=2 super QED with a single flavor. We find dual descriptions of a phase diagram containing four distinct massive phases. The equivalence of the intervening critical theories gives rise to several nonsupersymmetric avatars of mirror symmetry: we find dualities relating scalar QED to a free fermion and Wilson-Fisher theories to both scalar and fermionic QED. Thus, mirror symmetry can be viewed as the multicritical parent duality from which these nonsupersymmetric dualities directly descend.